CEO Power and Financial Reporting Quality: Investigating the Mediating Role of Audit Committee Effectiveness in Non-Financial Firms of Pakistan - Sheikh, Muhammad Azhar; Shoukat, Ayesha (JISR management and social sciences & economics, 2025)
This study investigates the association between financial reporting quality (FRQ), and CEO power in non-financial firms that are enlisted on the Pakistan Stock Exchange (PSX) and to explore whether the audit committee effectiveness (ACE) mediates the relationship between CEO Power and FRQ. The study uses a fixed-effects regression model to investigate the direct and indirect effects of CEO power on FRQ using a sample taken from the KSE 100 Index over a ten-year period from 2014 to 2023, comprising 604 firm year observations. The findings corroborate the predictions of agency theory by showing that CEO power has a negative impact on both FRQ and audit committee effectiveness. Additionally, mediation analysis highlights the relevance of governance systems in financial reporting oversight by confirming that ACE partially mediates the relationship between CEO Power and FRQ. Furthermore, the robustness model confirms the relationship between CEO power and FRQ as well as the mediation of ACE. The study offers implications for business scholars, leaders, and professional managers around the world as well as in Pakistan and contributes to the governance literature by documenting how concentrated managerial power weakens reporting quality. As per our findings which have theoretical and practical ramifications for shareholders, regulators, and legislators, stronger governance frameworks are necessary to reduce CEO dominance and improve the quality of financial reporting in Pakistan.